The death of us : a novel - Dean, Abigail (Viking, 2025)
"Late on a summer's evening when they are thirty years old, husband and wife Edward and Isabel's home is invaded by a serial killer. Theirs was a classic story of young love that moves into true partnership--but their solid foundation implodes in the wake of this violence. At fifty-eight, they are reunited for their tormenter's trial and forced to confront their lifelong love affair: the secrets, passions, and encounter that bind them still. Isabel has waited years for the man who nearly ended her life to be caught. As she's tracked news of his increasingly violent criminal life, she's connected with other survivors and prepared for the moment that she'd get to read her victim impact statement aloud in court. She is sure she'll speak her truth and finally let the past go. Edward has spent the years since the break-in--and the breakdown or his marriage--trying to figure out how a near-miss with death killed so much else in their shared life. Unlike Isabel, he's not eager to relive these terrible memories. Even though he's moved on--he's remarried, his old life almost unrecognizable to him now--he can't resist accompanying Isabel to their intruder's sentencing. What would revenge or justice feel like? Can closure set Isabel free? And what might that freedom mean for Edward?"--